Pelanggaran Maksim dalam Video Dakwah Gus Miftah di YouTube Tahun 2024: Studi Kasus dan Implikasinya: Violation of Maxims in Gus Miftah's Preaching Videos on YouTube in 2024: A Case Study and Its Implications - Mahadewi, Syahra; Ulfiyani, Siti; Kurniawan, Latif Anshori (JBSI: Jurnal Bahasa dan Sastra Indonesia, 2025)
The phenomenon of digital preaching through the YouTube platform has experienced rapid development and has become a strategic tool for disseminating religious values ??in the modern era. One prominent preacher in this context is Gus Miftah, known for his relaxed, humorous, and communicative preaching style. From a pragmatic perspective, this style of delivery exhibits several indications of maxim violations, both in terms of cooperation and politeness principles. This study aims to identify forms of maxim violations in Gus Miftah's preaching videos uploaded to YouTube throughout 2024 and analyze their implications for the audience. The research method employs a qualitative descriptive approach, utilizing a listening and note-taking technique based on transcripts of ten preaching videos. Data are analyzed based on the classification of maxim violations and the interpretation of the accompanying pragmatic functions. The results show various maxim violations, including the maxim of generosity, the maxim of quality, the maxim of relevance, and the maxim of quantity. The most dominant types of violations are the maxim of generosity and the maxim of relevance. These violations arise through the use of humor, satire, and social criticism, which serve as rhetorical strategies to attract attention, build emotional connection, and create a lively lecture atmosphere. However, violating maxims also has the potential to lead to multiple interpretations, misunderstandings, and adverse effects on the audience. Therefore, preachers in the digital era must consider the ethical aspects and context of language use to ensure that religious messages are conveyed clearly, educationally, and politely in public communication.